Efficacy of a transdiagnostic, video-based online program for reducing depression, anxiety, and suicidal ideation in adults: Protocol for a randomised controlled trial - Batterham, Philip J. (Contemp Clin Trials Commun, 2019)
BACKGROUND: Transdiagnostic online interventions have the potential to overcome help seeking barriers, address symptom comorbidity, and increase accessibility to evidence-based treatments. However, there is currently a lack of high quality studies examining brief transdiagnostic interventions, as well as research examining optimal methods for screening and providing members of the community with access to these interventions. This randomised controlled trial will compare a brief, video-based transdiagnostic online intervention (FitMindKit) to an attention matched control condition (HealthWatch). AIMS: The aims of the study are to (1) examine the efficacy of FitMindKit in reducing depression symptoms, anxiety symptoms, suicidal ideation, and disability relative to HealthWatch and (2) compare uptake of the program via the Internet with uptake via general practices and pharmacies (methods used in a parallel implementation study). METHODS: A two-arm randomised controlled trial will be conducted with adults residing in the Australian Capital Territory, Australia. Participants will be recruited online via social media advertisements, screened, and randomised to receive one of two four-week programs: FitMindKit (12-module psychotherapeutic intervention) or HealthWatch (12-module program providing general health information). Participants will be assessed at baseline and 4 weeks post-baseline. RESULTS: Findings from the trial will provide important knowledge regarding the utility and optimal implementation of brief transdiagnostic interventions for depression and anxiety in the community. CONCLUSIONS: This trial has strong potential to increase access to evidence-based treatments in the community by directly addressing several factors that impede this access, such as symptom comorbidity and a lack of knowledge regarding optimal implementation pathways. TRIAL REGISTRATION: This trial is registered with the Australian New Zealand Clinical Trials Registry (number ACTRN12618001688279).